PROTECTION OF THE POPULATION IN EMERGENCIES - Abdullayeva , Surayyo Munirovna (INTERNATIONAL CONFERENCES, 2023)
In ensuring the safety of human life, prevention, forecasting and elimination of the consequences of emergencies are of great importance. Today, when human economic activity leads to a violation of the ecological balance, the emergence of abnormal natural and man-made situations, the most urgent problem of our time is the organization of rescuing people, providing them with the necessary assistance, conducting emergency rescue operations in the lesions, preserving the health of the victims, reducing material damage, and along with it, there is such a problem as the training of specialists with higher education who are able to competently and skillfully organize the prevention of extreme situations and assist the population in eliminating danger.